A Simple and Practical Scheme Using Multiple Channels for Improving System Spectral Efficiency of Highly Dense Wireless LANs. (30th April 2019) - So, Jungmin; Lee, Joosang
Abstract : As the density of wireless LANs increases, performance degradation caused by hidden terminals and exposed terminals becomes significant. These problems come from carrier sensing based medium access control used in current wireless LANs. Hidden terminals are created if carrier sense threshold is too high, whereas exposed terminals are created if carrier sense threshold is too low. A good threshold depends on how far nodes are placed from their destinations, but that cannot be controlled by the system. In this paper, we propose a simple scheme that makes use of multiple channels. Multiple channels could be utilized by equipping multiple radios or using advanced hardware such as SDR to divide a single channel into multiple channels. Nodes are assigned channels based on their estimated distance from the AP. Once the assignment is done, carrier sense threshold for the channel is selected so that as many concurrent transmissions take place as possible, while preventing hidden terminals. Simulation results show that the proposed mechanism achieves significantly higher throughput without causing starvation at the edge nodes.